Non-traumatic depressed skull fracture in a neonate or 'ping pong' fracture. (18th February 2015) - Preston, David; Jackson, Simon; Gandhi, Salil
Abstract : This is a case study describing the finding of a depressed skull fracture in a neonate who was delivered without instrumentation and with no history of trauma. Depressed skull fractures are described as being associated with forceps delivery both vaginally and with caesarean section but are much rarer without instrumentation. This obvious abnormality was very concerning for the parents as it was not picked up on antenatal scans and there was no clear cause. There were both cosmetic and neurological concerns and we found no clear consensus on appropriate treatment and prognosis in the literature we had available.